CALCIUM INTAKE AND OBESITY ON ADOLESCENT GIRLS IN SURAKARTA - Dittasari Putriana; Nafilah Nafilah (Avicenna: Jurnal Ilmiah, 2022)
Background: The prevalence of obesity in children and adolescents continues to increase in recent years. In addition to genetic and environmental factors, calcium intake is one of the intake factors associated with Body Mass Index-for-age and waist circumference. This study aims to determine the relationship between calcium intake with BMI-for-age and waist circumference in adolescent girls in Surakarta. Methods: This study was an observational study with a cross sectional design involving 212 adolescent girls aged 15-18 years from 7 senior high schools (SMA) in Surakarta City. The research subjects were determined by the stratified random sampling method. Data of calcium intake was obtained from food recall 3 x 24 hours. Data of waist circumference was obtained by direct measurement. BMI-for-age was determined by calculating BMI-for-age using WHO Anthro Plus+ software to be presented in percentile form. Data analysis used Spearman's rank test with p<0.05. Results: The prevalence of obesity in adolescent girls based on BMI-for-Age and waist circumference were 13.2% and 16%, respectively. All respondents had low calcium intake (100%). There was no relationship between calcium intake with BMI-for-age (p=0.920; r=-0.007) and waist circumference (p=0.913; r=-0.008) in adolescent girls in Surakarta. Conclusion: There was no relationship between calcium intake with BMI-for-age and waist circumference. Adolescents need to increases the adequacy of calcium intake to prevent obesity.